Altered post-mortem metabolism identified in very fast chilled lamb M. longissimus thoracis et lumborum using metabolomic analysis. (October 2015) - Warner, Robyn D.; Jacob, Robin H.; Rosenvold, Katja; Rochfort, Simone; Trenerry, Craige; Plozza, Tim; McDonagh, Matthew B.
Abstract: The aim of this experiment was to use metabolomic techniques to investigate the energy metabolism in lamb M. longissimus thoracis et lumborum subjected to very fast chilling (VFC) post-mortem . The tissue was prepared by 2 different operators and subjected to very fast chilling (less than 0 °C within 1.5 h of slaughter) or typical chilling regimes (Control; 0 °C within 22 h of slaughter). Non-targeted metabolomic analysis ( 1 H NMR) and targeted analysis ( 31 P NMR, HPLC-PDA and HPLC–MS/MS) were used to examine the change in muscle metabolites post-mortem . One VFC treatment, which resulted in a colder core temperature and more tender meat, had higher levels of glycolytic intermediate metabolites pre-rigor as well as more of the end-products of adenosine and nicotine nucleotide metabolism pre-rigor, relative to conventionally chilled treatments. In conclusion, VFC to less than 0 °C within 1.5 h of slaughter causes considerable changes in metabolism and rigor onset, which are associated with tender meat. Highlights: Very fast chilling (VFC) was defined as muscle temperature below 0 °C early pre-rigor . Metabolomics was used to investigate changes in lamb muscles subjected to VFC. Muscles subjected to VFC had higher glycolytic intermediates pre-rigor . VFC muscles had more end-products of nucleotide metabolism pre-rigor. VFC caused considerable changes in metabolism and rigor onset, which were associated with tender meat.